Synthesis of Imidazoles and Pyrimidines Using Palladium-Catalyzed Decarboxylative Intramolecular Condensation of 1,2,4-Oxadiazol-5(4H)-ones - Shimbayashi, Takuya; Okamoto, Kazuhiro; Ohe, Kouichi (Synlett, 2014)
We found that 1,2,4-oxadiazol-5(4H)-ones acted as iminonitrene equivalents in the presence of a palladium catalyst and a stoichiometric amount of phosphine and that aza-Wittig-type condensation with the internal carbonyl moiety occurred to afford the corresponding imidazoles and pyrimidines.
Keywords: imidazoles; palladium; decarboxylation; aza-Wittig reaction